Расчет контактных давлений в механических системах с помощью программы Comsol Multiphysics - Байда, Евгений Иванович (НТУ "ХПИ", 2013)
В статье рассматривается методика расчета контактных давлений в осях механических систем при помощи пакета программ Comsol Multiphysics.

In the article, a calculation technique for contact pressure in the axes of mechanical systems based on Comsol Multiphysics package is considered.
Comsol multiphysics based calculation of contact pressure in mechanical systems
Keywords: электромеханические устройства; механические напряжения; рычажный механизм; ось вращения; mechanical system; contact pressure; calculation technique; Comsol Multiphysics